P251 Outcomes on a physician associate led ambulatory paracentesis service. (19th June 2022) - Ismail, Asem; Ishaq, Sauid; Mahmood, Rizwan; Frost, John; Silva, Shanika De; Rattehalli, Deepa; Shetty, Sharan; Fisher, Neil
Abstract : Introduction: Physician Associates (PAs) are part of the solution for addressing NHS healthcare shortages. One of the ways PAs can be utilised in gastroenterology is in supporting a day-case paracentesis service. We have looked at our outcomes of having a PA led ambulatory service in a district general hospital. Methods: A senior PA underwent training in paracentesis on the gastroenterology ward, and after achieving competency, was commissioned to lead the ambulatory service on our day case ward. A retrospective analysis of service performance from 2018 to 2020 was done. The main outcome measures were number of procedures performed, reasons for cancelled procedures and complications post-procedure; these details were obtained from electronic discharge letters. A random selection of patients (n=56) were also asked to complete a paper survey on their experience of the service. Results: A total of 372 elective ambulatory procedures were performed over the study period (76 in 2018, 118 in 2019 and 178 in 2020). The majority of these procedures (n=312, 83.9%) were done for cirrhotic patients. Successful procedures that were completed with no complications were 358 (The main complication post-procedure was that of ascites leakage at the entry site (n=11, 2.7%). Direct procedure related complications leading to unplanned admissions was 3 out of 372 cases (0.81%). These were one case of post-procedural bleeding, one case of persistent hypotension and one of significant pain resulting in the premature removal of the drain. There were no cases of viscus perforation. Twelve patients were admitted for reasons not relating to the procedure itself (n=6 for deranged blood tests, n=6 decompensated clinically i.e. encephalopathy). From the patients that were surveyed on their experience (n=56), 95% rated their overall experience as excellent or good. 91% of patients rated the technical ability of the performing practitioner as excellent and 93% rated the explanation of the procedure as excellent. Conclusions: Having a PA as a permanent team member who is always available without on-call responsibilities has helped in enabling the service to expand year on year. With appropriate training, having a PA led service may be both safe and effective, with overwhelmingly positive patient satisfaction.